El arbitraje como mecanismo alternativo de solución de conflictos y responsabilidades penales derivadas de él: algunas notas - Puente Rodríguez, Leopoldo (Pontificia Universidad Católica del Perú, 2025)
Arbitration has emerged as a prominent alternative to judicial adjudication for the resolution of disputes, gaining substantial social and economic significance. Despite its growing prominence, the role of criminal law in regulating and addressing misconduct within the arbitral process remains underexplored. This article posits that the existing criminal law framework is insufficiently equipped to effectively respond to potential criminal phenomena arising in the context of arbitration. Considering this, the study examines the current provisions and available responses within the Peruvian and Spanish criminal codes, highlighting both their strengths and limitations in confronting the unique challenges posed by arbitration-related offences.

El arbitraje, como sistema alternativo a la jurisdicción para la resolución de controversias, se encuentra en auge y su importancia social y económica resulta enorme. Sin embargo, esa creciente trascendencia de la institución no se ha visto acompañada de una reflexión acerca del papel que el Derecho penal debe desempeñar en todo este ámbito. La tesis central de este artículo es que el ordenamiento penal actual no se encuentra en condiciones de hacer frente satisfactoriamente a un eventual fenómeno criminal arbitral. En cualquier caso, se exploran algunas de las opciones penales disponibles a día de hoy en los códigos penales peruano y español.
Arbitration as an alternative dispute resolution mechanism and criminal law related to it: some reflections
Keywords: Arbitration; Arbitrators; Alternative dispute resolution; Bribery; Misconduct in public office; Prohibited negotiations; Arbitraje; Árbitros; Medios alternativos de solución de conflicto; Cohecho; Prevaricación; Negociaciones prohibidas; https://purl.org/pe-repo/ocde/ford#5.05.00